Phylogeny and historical biogeography of the lastreopsid ferns (Dryopteridaceae)1. Issue 7 (1st July 2014) - Labiak, Paulo H.; Sundue, Michael; Rouhan, Germinal; Hanks, Judith G.; Mickel, John T.; Moran, Robbin C.
Abstract : Premise of the study: As currently circumscribed, Lastreopsis has about 45 species and occurs in Australia, southern Asia, Africa, Madagascar, and the neotropics. Previous molecular phylogenetic studies suggested that Lastreopsis is paraphyletic. Our study focuses on resolving relationships among the lastreopsid ferns ( Lastreopsis, Megalastrum, and Rumohra ), the evolution of morphological characters, and an understanding of the temporal and spatial patterns that have led to the current diversity and geographical distribution of its extant species. Methods: Phylogenetic relationships were recovered under Bayesian, maximum likelihood, and maximum parsimony methods, using a data set of four plastid markers. Divergence time estimates were made using BEAST, and the biogeographic hypotheses were tested under the DEC model and the RASP/S‐DIVA methods. Key results: Lastreopsis was recovered as paraphyletic, and at least one of its clades should be recognized as a distinct genus, Parapolystichum . Coveniella poecilophlebia and Oenotrichia tripinnata were nested within Lastreopsis s.s., Megalastrum and Rumohra as sister to the Lastreopsis s.s., and the Lastreopsis amplissima clades. The initial diversification of the lastreopsids took place at about 56.55 Ma, from a neotropical ancestor. Conclusions: Taxonomic recognition of Parapolystichum is warranted to preserve the monophyly of Lastreopsis . Diversification among the main clades of the lastreopsid ferns was influenced by climatic and geological changes in the southern hemisphere. The biogeographic history of the group is intimately related to the trans‐Antarctic corridor between Australia and South America, with evidence for multiple lineage interchanges between Australia and South America during the Oligocene and the Eocene epochs.